2016
DOI: 10.1007/s11661-016-3345-6
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Selection and Microstructural Evolution in Directionally Solidified Tb0.3Dy0.7Fe1.95

Abstract: Tb 0.3 Dy 0.7 Fe 1.95 alloy was directionally solidified by using a modified Bridgman technique at a wide range of growth rates of 5 to 100 cm/h. The directionally grown samples exhibited plane front solidification morphology up to a growth rate of 90 cm/h. Typical island banding feature was observed closer to the chilled end, which eventually gave rise to irregular peritectic coupled growth (PCG). The PCG gained prominence with an increase in the growth rate. The texture study revealed formation of strong h31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…By comparing the texture at different distances from the onset of solidification, Palit et al [20] found that the transition in the preferred growth direction from <110> to <112> occurred through intermediate <123> texture components. Furthermore, plane-front solidification morphology and irregular peritectic coupled growth were observed in a wide range of solidification rates (5-80 cm/h), while the preferred direction changed from <311> to <110> to <112> at 5-100 cm/h solidification rates [21]. The {111} planes in Figure 2a were composed of two different types of atomic layers, in which one layer was all Fe, which increased the obstacle of atomic arrangement in the growth process.…”
Section: Grain Growth and Orientation Control During Directional Soli...mentioning
confidence: 97%
See 1 more Smart Citation
“…By comparing the texture at different distances from the onset of solidification, Palit et al [20] found that the transition in the preferred growth direction from <110> to <112> occurred through intermediate <123> texture components. Furthermore, plane-front solidification morphology and irregular peritectic coupled growth were observed in a wide range of solidification rates (5-80 cm/h), while the preferred direction changed from <311> to <110> to <112> at 5-100 cm/h solidification rates [21]. The {111} planes in Figure 2a were composed of two different types of atomic layers, in which one layer was all Fe, which increased the obstacle of atomic arrangement in the growth process.…”
Section: Grain Growth and Orientation Control During Directional Soli...mentioning
confidence: 97%
“…Figure 2. Comparison of atomic attachment kinetics at (a) (111) and (b) (311) interfaces; (c) magnetostriction (λ) of directionally solidified samples measured at an applied field of 5 kOe and (d)the plot of slope (dλ/dH) of the initial λ-H plot, plotted as a function of growth rate[21] (Adapted with permission from Ref [21]…”
mentioning
confidence: 99%